Venture capital : international comparisons - Green, Milford B. (Taylor and Francis, 2012)
First published in 1990, this is the first text to offer a goegraphicand regional study of venture capitalism. Although the importance of this type of capitalism in creating and nurturing small firms has long been recognized, it does not have a uniform global character. Drawing on previously unused data, Green's book offers a geographic comparison which displays the diverse forms of venture capitalist markets from the well established to the newly emerging and the rapidly disapearing.